Estrutura hospitalar e processos de trabalho envolvidos na assistência neonatal no Brasil - Menezes, Maria Alexsandra da Silva (2018)
Background: Despite the decrease and achieving the fourth target of the Millennium Development Goals, infant mortality is still high in Brazil. Neonatal mortality represents 60% of infant mortality. Almost one million neonatal deaths occur on the day of birth. Adequate hospital structure and high coverage of work processes in neonatal care, recommended by World Health Organization in the Essential Newborn Care program could reduce neonatal mortality. Objective: to assess hospital structure adequacy according newborns needs and to describe the coverage of Essential Newborn Care items in Brazilian neonatal care, next to childbirth. Methods: A cohort study was conducted between February 2011 and October 2012, in 266 public and private funding maternity hospitals of five major regions of Brazil including data of 23,894 postnatal women and their infants. We interviewed maternity hospitals managers and postnatal woman and we assay medical records of mothers and newborns. The proportions of newborns with high obstetric risk were analysed according to the presence of Neonatal Intensive Care Unit (NICU) and the level of adequacy of hospital structure. To analyse association between the categories, we used the chi-square test, considering p <0.05. Simple regression models were developed to estimate the strength of the associations between the dependent variable (non-access to each item of essential newborn care) and the hospital structure and maternal socio-demographics characteristics. In sequence, multiple regression models were developed with each dependent variable and the independent variables that proved significant in the first analysis. The odds ratios were adjusted, and 95% CI were estimated. Results: Only 10% of newborns with high obstetric risk were born in public maternity hospitals with NICU and with an adequate structure. In private sector, they were 8%. In public sector almost 50% of newborns with high obstetric risk were born in maternity hospital without NICU; that percentage rose to over 60% in the North, Northeast and non-capital cities. Antenatal corticosteroids were used in 41% of cases where this was indicated; this declined to 20% in the North and Mid-West and rose to 63.1% at private facilities. Early skin-to-skin contact occurred in 26.3% of births and in 39.7% of vaginal deliveries. 59.1% of all newborns were breastfed in their first hour of birth. Inadequate (ORa 2.16; CI95% 1.17-4.01) and without NICU beds (ORa 3.93; CI95% 2.34-6.66) maternity hospitals were the factors most associated with non-use of antenatal corticosteroids. Caesarean section was most associated with the absence of early skin-to-skin contact (ORa 3.07; CI95% 3.37-4.90) and absence of breastfeeding in the first hour of birth (ORa 2.55; CI95% 2.21-2.96). Conclusions: A great number of newborns with high obstetric risk were born in inadequate maternity hospitals. The coverage of the Essential Newborn Care items in Brazil is low, and varies depending on the characteristics of both the mother and the health facility where the delivery occurs. We found association between absence of use of antenatal corticosteroid and inadequate structure. Caesarean section was found as a risk factor to absence of early skin-to-skin contact and breastfeeding in the first hour of birth.